Progress in building-integrated solar thermal systems. (15th September 2017) - Maurer, Christoph; Cappel, Christoph; Kuhn, Tilmann E.
Highlights: Building integration of solar thermal is defined by its building-related functions. BIST has been 40% less expensive than conventional solar thermal installations. Suitable measurements to characterize BIST products are presented. Methods for better integration into the building process are described. Abstract: Solar building envelopes are attracting increasing interest. Building-integrated solar thermal (BIST) systems are one of the subgroups of solar building envelopes. This paper summarizes the most important contributions of recent years and extends them. First, BIST elements are defined and available BIST elements are presented. Then, the general functions which BIST systems can provide are presented and the conflict between the constant U and g values of simple planning software and the variable g and U values of BIST elements is discussed. Measurements to characterize BIST elements are presented as well as a design parameter space in which the current BIST elements are located and which can be used when developing innovative new components. Methods to evaluate and compare BIST technologies are presented. The substantial cost savings which were achieved in three building projects between 2002 and 2009 are discussed. Roles within the building process are presented, as well as the general methods and challenges for economic BIST calculations and one economic calculation as an example. Based on existing building processes, a vision for future BIST building process integration is presented. Simple BIST models, which need no programming, are provided with easy-to-use equations. The challenges of standards and regulations are outlined and future research topics are presented. This paper summarizes important recent contributions to BIST research as a basis for future progress in building-integrated solar thermal systems. Instead of aiming to cover all recent BIST developments, the focus is on BIST research findings which are relevant for cost reduction of BIST components and therefore necessary for the economic success of BIST technology. These are discussed, together with proposals for future research.